Association of pre-operative medication use with post-operative delirium in surgical oncology patients receiving comprehensive geriatric assessment. Issue 1 (December 2016) - Jeong, Young; Lee, Eunsook; Kim, Kwang-Il; Chung, Jee; In Park, Hae; Lee, Byung; Gwak, Hye
Abstract Background Older patients undergoing surgery tend to have a higher frequency of delirium. Delirium is strongly associated with poor surgical outcomes. This study evaluated the association between pre-operative medication use and post-operative delirium (POD) in surgical oncology patients receiving comprehensive geriatric assessment (CGA). Methods A total of 475 patients who were scheduled for cancer surgery and received CGA from January 2014 to June 2015 were included. Pre-operative medication review through CGA was conducted on polypharmacy (≥5 medications), delirium-inducing medications (DIMs), fall-inducing medications (FIMs), and potentially inappropriate medications (PIMs). POD was confirmed by psychiatric consultation, and DSM-V criteria were used for diagnosing delirium. The model fit of the prediction model was assessed by computing the Hosmer-Lemeshow goodness-of-fit test. Effect size was measured using the Nagelkerke R2 . Discrimination of the model was assessed by an analysis of the area under receiver operating curve (AUROC). Results Two models were constructed for multivariate analysis based on univariate analysis; model I included dementia and DIM in addition to age and sex, and model II included PIM instead of DIM of model I. Every one year increase of age increased the risk of POD by about 1.1-fold. DIM was a significant factor for POD after adjusting for confounders (AOR 12.78, 95 % CI 2.83-57.74). PIM was also a significant factor for POD (AOR 5.53, 95 % CI 2.03-15.05). The Hosmer-Lemeshow test results revealed good fits for both models (χ2  = 3.842, p  = 0.871 for model I and χ2  = 8.130, p  = 0.421 for model II). The Nagelkerke R2 effect size and AUROC for model I was 0.215 and 0.833, respectively. Model II had the Nagelkerke R2 effect size of 0.174 and AUROC of 0.819. Conclusions These results suggest that pharmacists' comprehensive review for pre-operative medication use is critical for the post-operative outcomes like delirium in older patients.